The Effects of Chromium and Tin Present in the Environment and Seawater on Biochemical Parameters in Male Rabbits - Citrine EL-Maleh,; Antisar Yunas,; Fayrouz Khaled, (AlQalam Journal of Medical and Applied Sciences, 2025)
The biochemical effects of exposure to potassium dichromate (K₂Cr₂O₇) and tin chloride (SnCl₂) on important liver and kidney function parameters and oxidative stress markers in experimental groups compared to controls are evaluated in this study. Male animals were split into three groups: a control group, a group that received K₂Cr₂O₇, and a group that received SnCl₂. Biochemical parameters, such as total protein, albumin, bilirubin, urea, creatinine, glucose, liver enzymes (AST and ALT), and plasma TBARS, were measured. The results showed that the K₂Cr₂O₇ and SnCl₂ groups had significantly lower levels of total protein and albumin than controls, indicating impaired protein synthesis. With SnCl₂ having a more noticeable effect, bilirubin levels were higher in the experimental groups, indicating hepatic impairment. Urea and creatinine levels rose as a result of both toxicants, indicating renal impairment, especially in the K₂Cr₂O₇ group. Both therapy groups had noticeably higher glucose levels, which is an indicator of metabolic problems. In line with hepatocellular damage, the experimental groups' hepatic enzyme activity (AST and ALT) was noticeably elevated. Furthermore, lipid peroxidation marker TBARS levels were markedly increased, indicating increased oxidative stress, with K₂Cr₂O₇ showing a greater effect. In summary, exposure to K₂Cr₂O₇ and SnCl₂ resulted in notable biochemical changes, with K₂Cr₂O₇ exhibiting more marked oxidative and nephrotoxic effects and SnCl₂ having a greater influence on hepatic function and protein synthesis. These results highlight the necessity of more investigation into these chemicals' toxicological processes. تقيم هذه الدراسة التأثيرات الكيميائية الحيوية لتعرض ثنائي كرومات البوتاسيوم وكلوريد القصدير على معايير وظائف الكبد والكلى الرئيسية، بالإضافة إلى علامات الإجهاد التأكسدي في المجموعات التجريبية مقارنة بالضوابط. تم تقسيم الحيوانات الذكور إلى ثلاث مجموعات: مجموعة ضابطة، ومجموعة تم إعطاؤها ثنائي كرومات البوتاسيوم، ومجموعة عولجت بـكلوريد القصدير. تم قياس المعايير الكيميائية الحيوية، بما في ذلك البروتين الكلي والألبومين والبيليروبين واليوريا والكرياتينين والجلوكوز وإنزيمات الكبد و المواد التفاعلية مع حمض الثيوباربيتيوريك في البلازما. كشفت النتائج عن انخفاض كبير في مستويات البروتين الكلي والألبومين في مجموعات كرومات البوتاسيوم وكلوريد القصدير مقارنة بالضوابط، مما يشير إلى ضعف تخليق البروتين. ارتفعت مستويات البيليروبين في المجموعات التجريبية، مما يشير إلى خلل في وظائف الكبد، مع ممارسة كلوريد القصدير لتأثير أكثر وضوحًا. تسبب كلا السمينين في زيادة مستويات اليوريا والكرياتينين، مما يعكس خللًا في وظائف الكلى، وخاصة في مجموعة كرومات البوتاسيوم . ارتفعت مستويات الجلوكوز بشكل ملحوظ في كلتا مجموعتي العلاج، مما يشير إلى اضطرابات التمثيل الغذائي. زادت أنشطة إنزيمات الكبد بشكل ملحوظ في المجموعات التجريبية، بما يتفق مع تلف الخلايا الكبدية. بالإضافة إلى ذلك، ارتفعت مستويات المواد التفاعلية مع حمض الثيوباربيتيوريك ، وهو مؤشر على بيروكسيد الدهون، بشكل ملحوظ، مما يسلط الضوء على الإجهاد التأكسدي المعزز، مع إظهار كرومات البوتاسيوم تأثيرًا أقوى. وفي الختام، تسبب التعرض لـ كرومات البوتاسيوم وكلوريد القصدير في حدوث تغييرات كيميائية حيوية كبيرة، حيث أظهر كرومات البوتاسيوم تأثيرات سامة للكلى وأكسدة أكثر وضوحًا، في حين كان لكلوريد القصدير تأثير أقوى على تخليق البروتين ووظيفة الكبد. وتؤكد هذه النتائج على الحاجة إلى مزيد من البحث في الآليات السمية لهذه المركبات